Xanthine oxidase inhibitory activity of a new isocoumarin obtained from Marantodes pumilum var. pumila leaves - Nor-Ashila Aladdin; Khairana Husain; Juriyati Jalil; Carla Wulandari Sabandar; Jamia Azdina Jamal (BMC, 2020)
Abstract Background In traditional Malay medicine, Marantodes pumilum (Blume) Kuntze (family Primulaceae) is commonly used by women to treat parturition, flatulence, dysentery, dysmenorrhea, gonorrhea, and bone diseases. Preliminary screening of some Primulaceae species showed that they possess xanthine oxidase inhibitory activity. Thus, this study aimed to investigate the xanthine oxidase inhibitory activity of three varieties of M. pumilum and their phytochemical compounds. Method Dichloromethane, methanol, and water extracts of the leaves and roots of M. pumilum var. alata, M. pumilum var. pumila, and M. pumilum var. lanceolata were tested using an in vitro xanthine oxidase inhibitory assay. Bioassay-guided fractionation and isolation were carried out on the most active extract using chromatographic techniques. The structures of the isolated compounds were determined using spectroscopic techniques. Results The most active dichloromethane extract of M. pumilum var. pumila leaves (IC50 = 161.6 μg/mL) yielded one new compound, 3,7-dihydroxy-5-methoxy-4,8-dimethyl-isocoumarin (1), and five known compounds, viz. ardisiaquinone A (2), maesanin (3), stigmasterol (4), tetracosane (5), and margaric acid (6). The new compound was found to be the most active xanthine oxidase inhibitor with an IC50 value of 0.66 ± 0.01 μg/mL, which was not significantly different (p > 0.05) from that of the positive control, allopurinol (IC50 = 0.24 ± 0.00 μg/mL). Conclusion This study suggests that the new compound 3,7-dihydroxy-5-methoxy-4,8-dimethyl-isocoumarin (1), which was isolated from the dichloromethane extract of M. pumilum var. pumila leaves, could be a potential xanthine oxidase inhibitor.